2016
DOI: 10.5603/piap.2016.0038
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive Sleep Apnea Syndrome and Hypothyroidism—Merely Concurrence or Causal Association?

Abstract: The prevalence of obstructive sleep apnea-hypopnea syndrome (OSAHS) ranges from 4 to 7% in men and from 2 to 5% in women. Its deleterious consequences such as traffic accidents, cardiovascular complications increasing morbidity and mortality, make it a major health problem. Apart from obesity (a major risk factor for OSAHS), hypothyroid patients are prone to reveal this phenotype. Although hypothyroidism seems an acknowledged risk factor for OSAHS, some authors report the lack of clinically relevant associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Hypothyroidism was also statistically associated with periodontitis and mild sleep apnea. Previous studies have been reported the association between OSA and hypothyroidism [ 35 36 ] and between hypothyroidism and periodontitis;[ 37 38 ] however, the physiopathology of these interrelationships has not been established and the association between hypothyroidism, periodontitis, and sleep apnea has not been previously documented. Diabetes mellitus was frequently observed in patients with OSA, but this association was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Hypothyroidism was also statistically associated with periodontitis and mild sleep apnea. Previous studies have been reported the association between OSA and hypothyroidism [ 35 36 ] and between hypothyroidism and periodontitis;[ 37 38 ] however, the physiopathology of these interrelationships has not been established and the association between hypothyroidism, periodontitis, and sleep apnea has not been previously documented. Diabetes mellitus was frequently observed in patients with OSA, but this association was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Glutamate is also an important neurotransmitter, which acts as a stimulant for brain activity. Thus, the abnormal ratio of GABA to glutamate may adversely affect the regulation of the sleepwake cycle (Kuczyński et al, 2016). OSA has been associated with sympathetic activation, excessive daytime sleepiness, and cognitive function changes.…”
Section: Role Of Sleep Disturbances In Cerebellar Malfunctionmentioning
confidence: 99%
“…Similarly, an older study reported that severe hypothyroidism is associated with depressed ventilatory drive during hypoxic and hypercapnic respiration (161). Adults with hypothyroidism often suffer from disordered breathing (162). However, in patients with obstructive sleep apnea, low thyroid hormones is not a common comorbidity (162,163).…”
Section: Hypothalamic-pituitary-thyroidal Axismentioning
confidence: 99%